Use of forest harvest residues: state of the art and opportunities (Research, Society and Development, 2021)
The present review of literature aimed to present the use of forest harvest wastes as source of biomass, since their generation to the possible end uses. Aimed still, list the main forest species grown in Brazil with potential to produce harvest wastes and, also, address the quantification and qualification of such biomass, and the market trends to their harnessing and utilization as high-value added products. Forest harvest wastes are the biomass left in the field after the collection of the wood trunks as logs and they include bark, leaves and treetops. Besides presenting the techniques of forest harvesting, this review shows the techniques to harness the harvest wastes and turn them into marketable products.